On the quasi-Lamb modes in hydroelastic waveguides - Bahno, O.M. (Reports of the National Academy of Sciences of Ukraine, 2018)
The propagation of quasi-Lamb waves in the systems "layer of ideal compressible fluid — elastic halfspace" and "elastic layer — half-space of ideal compressible fluid" is studied, by using the threedimensional equations of the classical elasticity theory for a solid body and linearized Euler equations for a fluid. The dispersion curves for normal waves over a wide range of frequencies are constructed. The influence of the thickness of elastic and fluid layers on the phase velocities and the dispersion of the quasi-Lamb modes in a hydroelastic waveguides is analyzed. Criteria for the existence of the quasi-Lamb waves in hydroelastic waveguides are proposed. The numerical results are presented in the form of plots and analyzed.